A delamination propagation model for glass fiber reinforced laminated composite materials - Aveiga Garcia, Jorge David (2018)
The employment of composite materials in the aerospace industry has been gradually considered due to the fundamental lightweight and strength characteristics that these type of materials offer. The science material and technological progress that has been reached, matches perfectly with the requirements for high-performance materials in aircraft and aerospace structures, thus, the development of primary structure elements applying composite materials became something very convenient. It is extremely important to pay attention to the failure modes that influence composite materials performances, since, these failures lead to a loss of stiffness and strength of the laminate. Delamination is a failure mode present in most of the damaged structures and can be ruinous, considering that, the evolution of interlaminar defects can carry the structure to a total failure followed by its collapse. Different techniques are usually adopted to accurately predict the behavior of damaged structures but, due to the complex nature of failure phenomena, there is not an established pattern. The present research project aims to develop a delamination propagation model to estimate a progressive interlaminar delamination failure in laminated composite materials and to allow the prediction of material\'s degradation due to the delamination phenomenon. Experimental tests assisted by ASTM Standards were performed to determine material\'s parameter, like the strain energy release rate, using GFRPs laminated composites. The delamination propagation model proposed was implemented as subroutines in FORTRAN language (UMAT-User Material Subroutine) with formulations based on the Fracture Mechanics. Finally, the model was compiled beside with the commercial Finite Element program ABAQUSTM.